Kompetensi Kepribadian Guru di SMK N 10 Padang - Sujarwati Sujarwati; Ermita Ermita; Nelitawati Nelitawati; Anisah Anisah (Journal of Educational Administration and Leadership, 2021)
The purpose of this study was to obtain information about the personal competence of teachers at SMK N 10 Padang in terms of: having a noble character, displaying a solid personality, displaying a wise person, an authoritative personality, a role model for students, showing a mature personality, and a stable personality. . This research is a descriptive research. This research is a population study involving all 55 teachers of SMK N 10 Padang. To see the validity and reliability of the data being tested, a Likert scale model questionnaire was used. Data were analyzed using the mean formula. The results of this study with the mean that the teacher is able to display: (1) noble character 4,3, (2) steady personality 4,1, (3) role model for students 4,19, (4) stable personality 4,04, (5) mature personality 4.0 (6) wise person 3.84 and (7) the teacher is quite capable of displaying an authoritative personality 3.49. So the Teacher Personality Competence at SMK N 10 Padang is in the criteria of being able with the result of 3.99.